2022
DOI: 10.1016/j.jarmac.2021.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Music evokes fewer but more positive autobiographical memories than emotionally matched sound and word cues.

Abstract: Anecdotal propositions that music is "special" as a memory cue have been partially supported by research demonstrating that music can evoke qualitatively different autobiographical memories than various other cues. However, it is unknown whether such differences in memory qualities may be attributed to inherent differences in properties of the retrieval cues.Across four online experiments, we tested whether unfamiliar musical retrieval cues exhibit differential effects on autobiographical memories when compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 54 publications
0
21
1
Order By: Relevance
“…Similarly, using environmental sounds as memory cues, Ernst and colleagues (2021) have recently shown that auditory cues were associated with an over-representation of repetitive events among the memories evoked by the five senses. Jakubowski and Eerola (2022) also demonstrated that music elicited fewer memories in comparison to environmental sound cues and word cues and that these memories were rated as less unique than word-cued memories. According to the model of Conway (Conway et al, 2019;Conway & Pleydell-Pearce, 2000), music would be more potent to trigger autobiographical memories related to the conceptual self, that cover a period of life or repeated events, than episodic autobiographical memories, that involve precise and time-limited episodes of life.…”
Section: Odours and Faces Outperform Music For Episodic Memorymentioning
confidence: 90%
See 2 more Smart Citations
“…Similarly, using environmental sounds as memory cues, Ernst and colleagues (2021) have recently shown that auditory cues were associated with an over-representation of repetitive events among the memories evoked by the five senses. Jakubowski and Eerola (2022) also demonstrated that music elicited fewer memories in comparison to environmental sound cues and word cues and that these memories were rated as less unique than word-cued memories. According to the model of Conway (Conway et al, 2019;Conway & Pleydell-Pearce, 2000), music would be more potent to trigger autobiographical memories related to the conceptual self, that cover a period of life or repeated events, than episodic autobiographical memories, that involve precise and time-limited episodes of life.…”
Section: Odours and Faces Outperform Music For Episodic Memorymentioning
confidence: 90%
“…Some studies suggested that other stimuli with strong ecological validity, such as music and faces, also demonstrate specificities for evoking episodic memory. Music-evoked autobiographical memories are reported to be consistently associated with strong emotions (Jakubowski & Eerola, 2022;Janata et al, 2007;Schulkind et al, 1999) and are also suggested to be very vivid (Belfi et al, 2016;Jakubowski et al, 2021). Interestingly, as for odours, the recognition performance of unfamiliar music is weaker than that of visual objects (Cohen et al, 2009(Cohen et al, , 2011Deffler & Halpern, 2011) and a recent study suggests that music elicited fewer memories in comparison to environmental sound and word cues (Jakubowski & Eerola, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have improved the AMT paradigm. Cues are no longer limited to words but range from verbal cues, such as words, to non-verbal cues, such as music [ 38 ], odor [ 39 ], and images [ 40 ]. Studies have approved the effectiveness of pictures as cues for autobiographical memory.…”
Section: Methodsmentioning
confidence: 99%
“…2D). Although recent work has investigated both involuntary and voluntary music-evoked autobiographical memories, in most studies participants were instructed to retrieve a memory in response to each music cue (Belfi et al, , 2022Sheldon et al, 2020;Sheldon & Donahue, 2017) or describe memories that came to mind during music exposure (Baird et al, 2018;Belfi et al, 2016;El Haj, Fasotti, et al, 2012;Jakubowski & Eerola, 2021). Therefore, even voluntary (as opposed to memory spontaneously evoked by music) retrieval in most prior studies consisted of responses directly to the music, rather than recall of separate memories.…”
Section: Specificity Of Music Exposure Effects On Memory Recallmentioning
confidence: 99%